Beyond links: understanding meaning and control in political blogs - Silva, Elsa Costa e (2016)
The use of hyperlinks in blogs produces hypertexts, which are characterized by an irregular and not sequential organization. Contrary to the narrative structures in which the author exercises his authority by setting an order of events, hypertexts compromise the integrity of authorship. Blog hyperlinking thus challenges traditional notion of authorship and control exercised over the speech produced. Political contexts, such as those inhabited by politicians and news providers, are quite sensitive to these compromises as control over meanings is seen as problematic. The use of a hyperlink can be seen as willingness to renounce to full control, but acknowledging its presence is insufficient to analyze its effects in the meaning of the posts. This article argues that a qualitative assessment of links is necessary if a full understanding of hyperlinks implications is to be provided. It proposes a model of analysis with three levels of compromising: referential, accessory, and compulsory.